Development of local technology for a small-scale biochar production processes from agricultural wastes (2010)
A charcoal fired reactor for small-scale production of biochar was successfully designed, fabricated and tested. The method of biochar production offered by this equipment was evaluated by comparing its output with a single barrel method of production. The results obtained during the test indicated that the efficiency of the equipment based on its output per kg of Cocoa pod husk was 79.9%. It has the capacity to produce 18.3 kg of Biochar from Cocoa Husk per day using 1 bag of local Charcoal. Cocoa pod Husk can be effectively used as raw material for Biochar production. The Specific Heat Capacity of Cocoa pod Husk was obtained as 3.8 kJ/kg K using the Choi and Okos model. The equipment can be afforded by small scale farmers at production cost of N24, 600.00.This machine can be easily used and maintained without any formal training. The reactor is therefore appropriate for use by subsistent farmers, and households for producing biochar on a small scale